Superheated atomization - Günther, Astrid; Wirth, Karl-Ernst (Process-Spray: Functional Particles Produced in Spray Processes, 2016)
The project “Superheated atomization", located at the Institute of Particle Technology (University of Erlangen-Nuremberg), focused on the characterization and evaluation of flash-or superheated-atomization. Flash atomization is based on a phase transition within or outside a nozzle, induced by a superheating prior to spraying. A multiphase flow can exists in the atomizer, containing bubbles with a higher inner pressure (corresponding to the vapor pressure of the sprayed fluid pv) than the ambient pressure p∞. These bubbles burst at the nozzle outlet, thereby disintegrating the fluid and generating a dispersed spray. Dependent on process conditions (e.g., fluid temperature T0), nozzle geometry (e.g., L/D-ratio) and fluid material properties (e.g. shear viscosity η) different spray morphologies occur. Furthermore spray properties like the characteristic mean droplet size (Sauter mean diameter x32) or spray temperature (Tm) are influenced by the flow conditions inside the nozzle. In order to characterize the resulting spray, the flow behavior inside the nozzle has to be analyzed. Therefore, measurements like mass flux determination are conducted. For the general characterization of the superheated atomization, plain water is used. Furthermore, more complex media like polyvinylpyrrolidone solutions are sprayed and differences are monitored. The results are combined with measurement data of the spray itself, like droplet velocities, determined with Particle Image Velocimetry (PIV), allowing a dimensionless description of the whole atomization process. The superheated atomization enables the generation of a finely dispersed spray with a variety of atomizer geometries. Due to the fact that the shear viscosity is lowered with increasing fluid temperature, comparably fine droplets size distributions are formed, even for rather high subcooled shear viscosity values. In respect to particle formation, it its advantageous that 2-10% of the fluid is evaporated as a side effect of the spraying process. Therefore, less liquid has to be removed in a downstream drying step for particle formatio